(3LRA ef GdbQBf GdcQje (B( (3GdLRA (B16)s
(3ChdgG (B:s
(3bGd JYGdi (B( (3bGd Cde Cbd dc Efc df JSJWjY eYi UHQkG , bGd Ef SCdJc Yf TF HYOgG adG JUGMHfi bO HdZJ ef dOfi YPQG s
(3BNQgG (B:s
(3bGd JYGdi (B( (3hGUWHQ YdjgG dGfSCdc QRbkG fMf fQRbc hGdYGbHI ddJbhi (B) (3UOb Gddg GdYXje s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdcJH GdSeGhjIs